Catheter ablation for atrial fibrillation in Patients after atrial Septal Defect repair - O. S. Stychynskyi; P. O. Almiz; N. S. Jaschuk; N. V. Melnik; A. V. Topchii; A. V. Pokanevych; O. А. Lozovoyi (Ukrainian Journal of Cardiovascular Surgery, 2019)
Atrial septal defect (ASD) is one of the most common congenital heart disorders. This defect is characterized by the development of atrial tachyarrhythmias, e.g. intra-atrial reentry or atrial fibrillation (AF).The objective of the study was to examine the safety and efficacy of AF ablation in patients after ASD repair. One-year procedural success was defined as freedom from recurrent AF, off antiarrhythmic drugs (complete freedom) or off/on previously failed antiarrhythmic drugs (complete/partial freedom).In total, 3 patients after ASD repair were included (the age was 40, 42 and 50; the time from cardiac surgery to catheter ablation was 23, 16 and 40 years; 2 patients had paroxysmal AF). Pulmonary vein isolaton was performed in 3 patients, of whom 2 underwent pulmonary vein isolation alone. Twenty six randomly selected patients undergoing first AF ablation at the same time period, without prior cardiac surgery and without concomitant structural cardiac pathology, were used as control. Peculiarity of ablation in the first group was the use of transesophageal and intracardiac echocardiography during transseptal puncture. Duration of the procedure was 190–220 minutes.Complete freedom was achieved within 14–18 months in 2 cases; complete/partial freedom was achieved in 1 case (no paroxysms of AF after antiarrythmic therapy in remote period). No complications were reported. The results were similar to those in the control group where complete freedom was observed in 20 (76.9%) and complete/partial freedom in 2 (7.7%) patients.AF catheter ablation in patients after ASD repair is effective and safe. It may be recommended as a priority technique for this group of patients.